The Grandparents in Children's Literature: gerontological and educational perspectives - Anne Carolina Ramos (Universidade Federal do Rio Grande do Sul, 2014)
This article examines representations of grandparents in Brazilian children's literature. Understanding children's literature as a cultural pedagogy, it discusses the contexts and images of old age and grandparenthood that have been disseminated by children's books, as well as the links between identities of gender and of generation. Enlacing the fields of Gerontology and Pedagogy, it seeks to understand the truths and the knowledge that have been taught to children about old age, grandparenthood and intergenerational relations, bringing reflections to the studies of ageing and education.